2007
DOI: 10.1209/0295-5075/81/30007
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and the quantum brachistochrone problem

Abstract: Entanglement is closely related to some fundamental features of the dynamics of composite quantum systems: quantum entanglement enhances the "speed" of evolution of certain quantum states, as measured by the time required to reach an orthogonal state. The concept of "speed" of quantum evolution constitutes an important ingredient in any attempt to determine the fundamental limits that basic physical laws impose on how fast a physical system can process or transmit information.Here we explore the relationship b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 14 publications
1
44
1
Order By: Relevance
“…The advantage increases for C in this game for increasing N because the opportunities for C are N/2 while Q has only one. As quantum entanglement enhances the "speed" of evolution of certain quantum states [23] in future analysis we will introduce entanglement between players in order to see if it provides any advantage to entangled players and changes the stable solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage increases for C in this game for increasing N because the opportunities for C are N/2 while Q has only one. As quantum entanglement enhances the "speed" of evolution of certain quantum states [23] in future analysis we will introduce entanglement between players in order to see if it provides any advantage to entangled players and changes the stable solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Borras et al [15,16] showed that quantum brachistochrone evolution between orthogonal states cannot be implemented without the typical entanglement of two subsystems (such as linear entropy or concurrence). For a three-qubit entangled quantum system, its concurrence satisfies the following relation,…”
Section: Time Averaged Entanglement During Brachistochrone Evolutionmentioning
confidence: 99%
“…Rev. A 80, 052106 (2009) † Email: fgdeng@bnu.edu.cn orthogonal and nonorthogonal, pure and mixed, as well as bipartite and multipartite cases [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimization of this time is as important, from the experimental point of view, as the gate complexity. A considerable amount of work has recently been devoted to the time-optimal quantum computation problem, with emphasis in the quantum Brachistochrone formalism [21,22,23,24]. Making use of the analogy with the brachistochrone problem from classic mechanics, Carlini et.…”
Section: Introductionmentioning
confidence: 99%